Assessment and impact of quality of life in patients who underwent dental bleaching in the office (Research, Society and Development, 2022)
Aesthetic dentistry is an important guide for improving social relationships, aimed at promoting self-esteem and well-being, resulting in people's quality of life. The present study aims to verify the impact of in-office tooth whitening on the quality of life of patients at the Clinical School of Dentistry (CEO) of the Federal University of Campina Grande, campus Patos, Paraíba (PB), before and after the whitening procedure. This was a cross-sectional, observational study, with an inductive approach and a comparative, descriptive procedure, adopting the Oral Health Impact Profile (OHIP-14) as a strategy, with a sample of 60 patients. Aspects such as: characterization of patients (age and gender) and information on oral health and quality of life (functional limitation, physical pain, psychological discomfort, physical, social, psychological incapacity, and social disadvantage) were addressed. With the results obtained, it was observed that almost all patients (96.7%) had an impact of oral health on quality of life before the whitening procedure, decreasing the impact to (91.7%) after treatment. The prevalence of impact was higher in the domains of physical pain and psychological discomfort, the latter being the one with the greatest decrease in impact after tooth color change, going from 80% (before) to 53.3% (after). It was possible to conclude that the impact of quality of life in relation to tooth whitening was more relevant with regard to psychological discomfort, showing that the color of teeth is a factor that brings positive changes in the individual's psychosocial well-being.